Knowledge of Nurses and Midwives on Risk Factors Associated with Osteoporosis - Poran Mokhtari; Parvin Shiri; Elahe Ahmadnia; Tarane Khooshehchin (Zanjan University of Medical Sciences and Health Services, 2011)
Background and Objectives: This study aimed to investigate nurses' and midwives' current knowledge about the osteoporosis.   Material and Methods: In this survey, we used the FOOQ (The Facts on Osteoporosis Quiz) questionnaire to measure osteoporosis knowledge on 214 nurses and midwives in Valiasr hospital in Zanjan.   Results: Findings indicated a generally moderate to high level of knowledge about certain risk factors among the participants. The main deficit in the knowledge of the participants was about walking and bone health.   Conclusion: The study findings were consistent with the results of other studies which have reported that the knowledge of osteoporosis among nurses and midwives is less than adequate. The findings showed the requirement to focus on in the osteoporosis educational interventions among nurses and midwives.